How to conduct cost and value analyses in health professions education: AMEE Guide No. 139. (2nd September 2021) - Foo, Jonathan; Cook, David A.; Tolsgaard, Martin; Rivers, George; Cleland, Jennifer; Walsh, Kieran; Abdalla, Mohamed Elhassan; You, You; Ilic, Dragan; Golub, Robert; Levin, Henry; Maloney, Stephen
Abstract: Growing demand for accountability, transparency, and efficiency in health professions education is expected to drive increased demand for, and use of, cost and value analyses. In this AMEE Guide, we introduce key concepts, methods, and literature that will enable novices in economics to conduct simple cost and value analyses, hold informed discussions with economic specialists, and undertake further learning on more advanced economic topics. The practical structure for conducting analyses provided in this guide will enable researchers to produce robust results that are meaningful and useful for improving educational practice. Key steps include defining the economic research question, identifying an appropriate economic study design, carefully identifying cost ingredients, quantifying, and pricing the ingredients consumed, and conducting sensitivity analyses to explore uncertainties in the results.